Pembuatan Biogas dari Rumput Laut Jenis Caulerpa racemosa dan Sargassum duplicatum sebagai Bahan Energi Alternatif - Saputra, Andrian; Putri, Wike Ayu Eka; Aryawati, Riris (Maspari Journal : Marine Science Research, 2011)
Seaweed has economic value that is very important for humans. Several years ago, only seaweed used as human food ingredients. Given the many types of seaweed are still not popular yet widely used and Along with the progress of science and technology, utilization of seaweed has expanded in various fields, including one uses seaweed as an ingredient of biogas alternative energy. The purpose of this study was to determine the potential of seaweed species Sargassum duplicatum and Caulerpa racemosa for the manufacture of biogas as a new alternative energy sources and to know the pressure of gas contained in a type of seaweed Sargassum duplicatum and Caulerpa racemosa as a new alternative energy sources. This research was conducted in June-September 2010. Samples were taken in waters around Lampung Marine Aquaculture Development Center. Making biogas process is conducted at the Laboratory of Marine Science. Faculty of Mathematics and Natural Sciences, Sriwijaya University. The method used is a laboratory experimental methods. Making biogas is done by collecting seaweed and beach sediments as seedman making, preparation of the digester and the making of starter and stuffing, were examined by using biogas pressure manometer U for three months, analyze the data descriptively biogas pressure. Based on the results of research in getting the peak pressure for this type of seaweed Sargassum duplicatum is 15.47 psi, 16.05 psi and 16.43 while to get the type of Caulerpa racemosa in the peak pressure of 15.42 psi, 15.88 psi and 16, 43 psi. Keywords: Seaweed, Biogas, Sargassum duplicatum, Caulerpa racemosa, Biogas pressure. ABSTRAK Rumput laut memiliki nilai ekonomis yang sangat penting bagi manusia. Beberapa tahun yang lalu, rumput laut hanya dimanfaatkan sebagai bahan makanan manusia. Mengingat masih banyaknya jenis rumput laut tidak popular yang belum banyak dimanfaatkan dan sering dengan kemajuan sains dan teknologi, pemanfaatan rumput laut telah meluas di berbagai bidang, termasuk salah satunya pemanfaatan rumput laut sebagai bahan energi alternatif yaitu biogas. Tujuan penelitian ini adalah mengetahui potensi rumput laut jenis Sargassum duplicatum dan Caulerpa racemosa untuk pembuatan biogas sebagai sumber energi alternatif baru serta mengetahui tekanan gas yang terdapat dalam rumput laut jenis Sargassum duplicatum dan Caulerpa racemosa sebagai sumber energi alternatif baru. Penelitian ini dilaksanakan pada bulan Juni – September 2010. Pengambilan sampel dilakukan di sekitar perairan Balai Pengembangan Budidaya Laut Lampung. Proses Pembuatan biogas itu sendiri dilakukan di Laboratorium Dasar Ilmu Kelautan. Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Sriwijaya. Metode yang digunakan adalah metode eksperimental laboratoris. Pembuatan biogas ini dilakukan dengan cara pengumpulan rumput laut dan pengambilan sedimen pantai sebagai penyemai, penyiapan digester serta pembuatan starter dan isian. Dilakukan pengamatan tekanan biogas dengan menggunakan manometer U selama tiga bulan. Analisa data tekanan biogas dilakukan secara deskriptif. Berdasarkan hasil penelitian di dapatkan tekanan puncak untuk jenis rumput laut